Genetic variations of gliadin and high-molecular-weihht glutenin subunits in diploid wheats - Cai Ma, Z.=700 1 Wei, Y.M.; Yan, Z.H.
(En, Fr, Es)
ilus., 26 ref.
Keywords: TRITICUM; VARIACION GENETICA; PROLAMINAS; GLUTENINAS; ITALIA